Effect of ginseng stem leaf extract on the production performance, meat quality, antioxidant status, immune function, and lipid metabolism of broilers - Zhang, Peng; Zhang, Haoyue; Ma, Chuanjie; Lv, Qiufeng; Yu, Haiyang; Zhang, Qiang (Frontiers in Veterinary Science, 2024)
IntroductionThe present study explores the effect of ginseng stem leaf (GSL) extract on the production performance, meat quality, antioxidant status, immune function, and lipid metabolism of white feathered broilers.MethodsThere were 6 replicates in each group, with 10 broilers in each replicate. In the 42 day trial, 300 AA broilers were randomly divided into five groups: control group (CON), 1.25% GSL extract group (GSL-L), 2.5% GSL group (GSL-M), 5% GSL group (GSL-H), and 45 mg/kg chlortetracycline group (CTC).ResultsThe results showed that different doses of GSL extract could improve the body weight, feed to gain ratio (F/G), average daily feed intake (ADFI), average daily gain (ADG), and meat quality of broilers. Compared with the control group, the addition of different doses of GSL improved the antioxidant and immune abilities of broilers to varying degrees, and the effect of GSL extract was significant in the GSL-H group (p < 0.05). In addition, medium and high doses of GSL extract significantly reduced the blood triglyceride (TG) and total cholesterol (TC) contents of broilers (p < 0.05).DiscussionAdding GSL extract to the feed has a positive impact on the body weight, meat quality, antioxidant capacity, immunity, and blood lipids of broilers.